Relaciones Económicas China-Japón: Los dos gigantes de Asia cada vez más integrados - Aquino Rodríguez, Carlos (2010)
China and Japan are the second and third largest economies in the world now and continue to increase their economic relationship as they need each other. Japan needs China cheap labor force and its big internal market, while China needs Japan technology, capital and management know how. Japan through history learned many things from China even if during a period both countries encountered difficult times. As they need each other Japan and China will continue to get closer.